Adiabatic investigation of the electronic and dipolar properties of the LiNe system in ground state and numerous excited states. (November 2021) - Ayed, Mouna Ben Hadj; Mtiri, Safa; Ghalla, Houcine
Abstract: Using ab-initio adiabatic calculation, we studied the electronic properties of the LiNe molecule. In our calculation, we investigate the adiabatic potential energy curves (PECs) of numerous 2 Σ +, Π and Δ electronic states. Then, we derive spectroscopic constants, as well as their vibrational levels spacing. For the 2 Σ + states, we determined the permanent and transition dipole moment (PDM and TDM). Our approach is based on the full configuration interaction (FCI), an effective core potential (ECP) which describes the valence electron of the molecule, and the core polarization potential (CPP). Using a large Gaussian basis set, a full configuration interaction is easily carried out.